Methods for meaningful text representation and comparison - Devitt, Ann (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2005)
This thesis investigates methods of text representation and comparison using WordNet as a real world knowledge base. The research is carried out within the framework of lexical cohesive theory which defines the cohesive structure of text built through the connections and interactions of its constituent lexical items. The model of cohesive structure explored in this thesis is a network of interrelated lexical items.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin